The growth Shorea leprosula Miq. on various slopes and directions of slopes in Gunung Dahu Research Forest, Bogor - Prijanto Pamoengkas; Henti Hendalastuti Rachmat; Hana Afiana (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Shorea leprosula Miq is a Dipterocarps forest plantation that has the prospect of being developed because it is a fast-growing species with high economic value. Given its commercial importance, this study was conducted to analyze the effect of slope class and slope direction on growth. Data were collected using the census method on S.leprosula stands with a spacing of 2m x 2m and 4m x 8m. The direction of the slope is determined based on the configuration of the slope according to the cardinal directions, while the slope of the land is determined based on the classification of the slope class of the land. The results showed that the slope class, slope direction, and the interaction between factors had a significant effect on the growth of S.leprosula. The interaction between the slope class and the direction of the slope produces the highest average annual increment of diameter in the flat slope class with the direction of the slope facing north, which is 1.79 m / year while the highest annual increment of the total average height is in the very steep slope class with to the slope facing to the north at 0.82 m / year.